Reliability of a digital system for models measurements in BBO grading: A pilot study - Paula Martins Bravo MIRANDA; Luciana Quintanilha Pires FERNANDES; Manuel Gustavo Chavez SEVILLANO; Felipe de Assis Ribeiro CARVALHO; Jonas CAPELLI JUNIOR (Dental Press Editora, 2022)
ABSTRACT Introduction: Currently, no method is considered effective for the evaluation of digital models in the Certification Examination of the Brazilian Board of Orthodontics (BBO), considering the parameters of the currently used manual method. Objective: Thus, the aim of this study is to verify the reliability of an evaluation method for digital models that could be used in the BBO exam, compared to the gold standard. Methods: Measurements were performed by five previously calibrated examiners. Samples of ten sets of plaster models of the final phase of orthodontic treatment were measured using a manual method (Objective Grading System, OGS). These models were digitized using a 3D scanner and exported to Geomagic Qualify software, in which the measurements were made with the proposed digital method. These measurements were repeated using five models, after fifteen days. The intra-examiner performance with this method was analyzed with a paired t-test, whereas the inter-examiner analysis was carried out with analysis of variance and Tukey's test. To compare the manual and digital methods, a paired t-test and Pearson's correlation analysis were performed. Results: A statistically significant difference was found. The results showed that, when compared to the manual method, the digital method was effective in measuring the OGS in four of the seven variables studied: Marginal Ridge, Overjet, Occlusal Contact, and Interproximal Contact. The variables Alignment, BL inclination, and Occlusal Relationship showed a great amount of dispersion in the findings. Conclusion: Further studies are needed to develop an adequate digital methodology that can be used for all OGS variables.